The right to life and the omissions to the right to health and the rights of the patient, in the Peruvian constitution - Tapia Tapia, Sergio Carlos Baltazar (2022)
The Political Constitution of Peru of 1993, has been subject to various modifications -in the almost 30 years of validity- and for a little over a year changes have been proposed from a maximalist position that promotes the substantial reform of the social and economic model, as well as from minimalist positions, some adjustments are proposed in specific aspects. But, what is central in every fundamental letter is the human being, both the conception of him and his position against the powers of those who exercise the authority of the state. In this matter there is no reform to specify, no enrichment to perfect and no update to support the clear notion of the human person in the various stages of its existence (conception, embryonic, fetal and postpartum). The right to life -which enjoys constitutional recognition-, which is closely related to the right to health, is not properly legislated in the constitutional text. Neither are the rights of the patient, nor the rights of every human being in the face of scientific and technological research, nor the right to palliative care that resolves the dilemmas of the end of life. The rights demand a convenient constitutional regulation, which cannot be postponed. It is, then, urgent to assume bioethical principles to formulate an effective defense of human life, clarifying the right to health, granting effective guarantees of compliance with medical care benefits y regulate scientific and technological research should not be neglected, when the human being becomes an object of experimentation, including the moment of conception and its embryonic development.